A new species and two new records of Stemonitidaceae from China - Bo, Zhang; Yu, Li (Phytotaxa, 2016)
A new species of Stemonitidaceae, Comatricha clavicolumella, collected in Jigong Mountain Scenic Area, Henan Province, China, is described. C. clavicolumella has a columella that usually ends in a clavate expansion at the apex of the sporocysts, and has smaller spores than usual for the genus (about 5–5.5 μm in diam.). Two newly recorded species from China, C. ellae and C. reticulospora, are also described. We present a scanning electron micrograph study of the species.